Systematically lower aEEG amplitude values in neurologically healthy children using an automated algorithm compared to a semi-manual method - Greve, Sandra Julia Nicole; Brensing, Pia Sophie; Paul, Luisa; Dohna-Schwake, Christian; Wichlacz, Julia; Felderhoff-Mueser, Ursula; Bruns, Nora (Frontiers in neurology, 2025)
ObjectiveThe objective of this study was to compare different modes of amplitude-integrated EEG (aEEG) assessment (semi-manual vs. automated) in children.MethodsA total of 450 unremarkable pediatric EEGs from children aged 6 months to 17.9 years were converted into aEEGs and the medians and means of the upper and lower amplitudes (C3-P3, C4-P4, C3-C4, P3-P4, Fp1-Fp2) were determined. The agreement of the semi-manual and automated measurements was assessed via the Pearson correlation coefficients (PCC) and Bland-Altman plots. Mean differences between the methods and age-specific percentiles (5th−95th) were calculated.ResultsSemi-manually measured amplitudes were systematically greater than automated assessments. Mean differences of the means ranged between 23.7 and 29.3 μV for the upper and between 2.4 and 4.4 μV for the lower amplitudes depending on the channel. The PCC ranged between 0.68 and 0.92 for the upper and lower amplitudes of the mean depending on the channel. Age-specific percentiles showed different absolute values but similar trends.ConclusionAEEG amplitude values systematically differ between semi-manual and automated assessment. Age-related trends are evident despite differences in the absolute values. Reference values for different measurement techniques are needed for pediatric aEEG.
Gesehen am 23.01.2026